Breathing under Anesthesia: A Key Role for the Retrotrapezoid Nucleus Revealed by Conditional Phox2b Mutant Mice. (June 2019) - Bourgeois, Thomas; Ringot, Maud; Ramanantsoa, Nelina; Matrot, Boris; Dauger, Stéphane; Delclaux, Christophe; Gallego, Jorge
Editor's Perspective: What We Already Know about This Topic: Many if not all drugs used in anesthesia and analgesia can produce potentially severe respiratory depression Maintenance of breathing under anesthesia is linked to the drive exerted by the retrotrapezoid nucleus on the respiratory central pattern generator The retrotrapezoid nucleus neurons that stimulate breathing during anesthesia are carbon dioxide–sensitive noncatecholaminergic neurons that express Phox2b, a master gene for the development of autonomic neurons The conditional mouse model with the +7Ala repeat mutation targeted to the retrotrapezoid nucleus ( Phox2b 27Alaki/+ mice) present a massive selective loss of retrotrapezoid nucleus neurons and lack carbon dioxide chemosensitivity at birth but survive normally and partially recover carbon dioxide chemosensitivity in adulthood What This Article Tells Us That Is New: Ketamine, propofol, and fentanyl caused lethal respiratory failure in most mice with selective genetic loss of retrotrapezoid nucleus neurons, at doses that were safe in their wild type littermates Background: Optimal management of anesthesia-induced respiratory depression requires identification of the neural pathways that are most effective in maintaining breathing during anesthesia. Lesion studies point to the brainstem retrotrapezoid nucleus. We therefore examined the respiratory effects of common anesthetic/analgesic agents in mice with selective genetic loss of retrotrapezoid nucleus neurons ( Phox2b 27Alacki/+ mice, hereafter designated "mutants"). Methods: All mice received intraperitoneal ketamine doses ranging from 100 mg/kg at postnatal day (P) 8 to 250 mg/kg at P60 to P62. Anesthesia effects in P8 and P14 to P16 mice were then analyzed by administering propofol (100 and 150 mg/kg at P8 and P14 to P16, respectively) and fentanyl at an anesthetic dose (1 mg/kg at P8 and P14 to P16). Results: Most mutant mice died of respiratory arrest within 13 min of ketamine injection at P8 (12 of 13, 92% vs. 0 of 8, 0% wild type; Fisher exact test, P < 0.001) and P14 to P16 (32 of 42, 76% vs . 0 of 59, 0% wild type; P < 0.001). Cardiac activity continued after terminal apnea, and mortality was prevented by mechanical ventilation, supporting respiratory arrest as the cause of death in the mutants. Ketamine-induced mortality in mutants compared to wild types was confirmed at P29 to P31 (24 of 36, 67% vs. 9 of 45, 20%; P < 0.001) and P60 to P62 (8 of 19, 42% vs. 0 of 12, 0%; P = 0.011). Anesthesia-induced mortality in mutants compared to wild types was also observed with propofol at P8 (7 of 7, 100% vs . 0 of 17, 7/7, 100% vs. 0/17, 0%; P < 0.001) and P14 to P16 (8 of 10, 80% vs. 0 of 10, 0%; P < 0.001) and with fentanyl at P8 (15 of 16, 94% vs . 0 of 13, 0%; P < 0.001) and P14 to P16 (5 of 7, 71% vs . 0 of 11, 0%; P = 0.002). Conclusions: Ketamine, propofol, and fentanyl caused death by respiratory arrest in most mice with selective loss of retrotrapezoid nucleus neurons, in doses that were safe in their wild type littermates. The retrotrapezoid nucleus is critical to sustain breathing during deep anesthesia and may prove to be a pharmacologic target for this purpose. Abstract : Ketamine, propofol, and fentanyl caused lethal respiratory failure in most mice with selective genetic loss of retrotrapezoid nucleus neurons, at doses that were safe in their wild type littermates.Supplemental Digital Content is available in the text.